Compressive strength and durability properties of high volume fly ash concretes containing ultrafine fly ash - Shaikh, Faiz; Supit, S. (ELSEVIER, 2015)
This paper presents the effect ultrafine fly ash (UFFA) on compressive strength and durability properties of concretes containing high volume class F fly ash as partial replacement of cement. The compressive strengths are measured at 3, 7, 28, 56 and 90 days, whereas the durability properties are measured at 28 and 90 days. Chloride induced corrosion, water sorptivity, volume of permeable voids, chloride ion penetration, chloride diffusivity and porosity of above concretes are measured in durability properties. Microstructural analysis in terms of thermogravimetric analysis (TGA) is also conducted to identify the reaction phases of calcium hydroxide in the HVFA matrix containing UFFA. Results show that the addition of 8 wt.% UFFA significantly improved the early age as well as later age compressive strengths of ordinary and HVFA concretes. All above measured durability properties of HVFA concretes are also improved and in most cases the HVFA concrete containing 32% fly ash and 8% UFFA exhibited superior durability properties than ordinary concrete containing 100% cement. The results also indicate the effectiveness of UFFA in producing high packing density and in accelerating the pozzolanic activity to produce more C–S–H gel by consuming calcium hydroxide (CH) in HVFA concretes.